Morphometry and distribution patterns of Melocactus violaceus subsp. margaritaceus (Cactaceae), in two contrasting Brazilian ecosystems - Larios Ulloa, Mauricio; Vinicius Meiado, Marcos; Loza Cornejo, Sofía; da Conceiҫão Santos, Katiane (Instituto de Ecología, A.C., 2019)
Background and Aims: Melocactus violaceus an endemic cactus distributed in eastern Brazil, is classified as a vulnerable species in the IUCN Red List due to habitat loss. This research was conducted in two contrasting Brazilian ecosystems, caatinga (Serra de Itabaiana National Park) and restinga (Pirambu beach), with the aim of determining the distribution patterns, density, vegetative morphometric characters (height and diameter of the stem) and reproductive characters (presence of cephalium, morphology of flower, fruit and seed) of this subspecies and highlight the possible influence of the habitat on its populations. Methods: For each of the study areas, patterns of distribution, density, mortality index, morphometric characters of vegetative (height and diameter stem) and reproductive structures (length and diameter of flower, fruit and seed) were analyzed through statistical analyses (ANOVA, Tukey multiple comparison tests and Pearson correlation coefficients). Key results: The results showed a density of 0.52 and 0.44 individuals/m2 in caatinga and restinga, respectively. More than 65% of individuals establish themselves in vegetation-free patches in both zones. The average values of morphometric characters are within those established for the subspecies, although significant statistical differences were observed (p<0.05) when comparing the two study sites. The Pearson correlation coefficients were significant for the variables fruit length vs. fruit diameter (r=0.9909) and fruit length vs. flower diameter (r=0.9907). Conclusions: In caatinga, there was a greater density and death rate, whereas a greater percentage of individuals with cephalium was registered in restinga. The registered differences would represent an indication of the probable environmental influence, particularly of microhabitat on some morphometric characters of individuals.